Analýza zdravotních a enviromentálních rizik v Teplárnách Brno a.s. - Mercová, Denisa (Vysoké učení technické v Brně. Ústav soudního inženýrství, 2024)
Diplomová práce se věnuje analýze rizik v Teplárnách Brno, které při svých činnostech využívají nebezpečné chemické látky. Teoretická část práce se věnuje souvisejícím pojmům a právním požadavkům pro zhodnocení možných rizik v souvislosti s nebezpečnými látkami. Praktická část seznamuje s vybranou firmou a pomocí analýz vyhodnocuje přijatelnost zjištěných rizik a následná navržená opatření ke snížení pravděpodobnosti výskytu identifikovaných rizik.

The diploma thesis is devoted to risk analysis in Teplárny Brno, which use dangerous chemical substances in their activities. The theoretical part of the work is devoted to related concepts and legal measures for evaluating possible risks in connection with dangerous substances. The practical part introduces the selected company and, using the analyses, evaluates the acceptability of the identified risks and subsequent suggested measures to reduce the probability of the occurrence of the identified risks.
Analysis of Health and Environmental Risks in Teplárny Brno a.s.
Keywords: Nebezpečná látka; riziko; nebezpečí; závažná havárie; krizový management; Dangerous substance; risk; danger; serious accident; crisis management